Preparation and characterization of jute fiber reinforced shellac biocomposites: effect of additive - Khan, Mubarak; Ghoshal, Sushanta; Khan, Ruhul; Pervin, Shamim-Ara; Mustafa, Ahmed (Publishing House of Lviv Polytechnic National University, 2008)
Hessian cloth (jute fabrics) samples were soaked in the alcoholic shellac solution and dried at 333 K for 4 hours. Six layers of shellac treated hessian cloth were heat pressed (373 K for 10 min at 5 MT pressure) to fabricate biocomposite and then its mechanical properties were evaluated. To improve the mechanical properties of the biocomposite, a series of formulations was prepared using varying percentages of urea (0.25 to 30 %) with shellac in methanol; then the composite was fabricated using same parameters. Mechanical properties such as tensile strength (TS), bending strength (BS), tensile modulus (TM), bending modulus (BM), elongation at break (Eb), impact strength (IS) of the biocomposite were determined. Percentage of urea and soaking time of hessian cloth for the composites were optimized over mechanical properties. The biocomposite prepared with 0.5 % urea at 2 min soaking time showed the highest mechanical properties (TS – 79 MPa, BS – 74 MPa, BM – 7 GPa, IS – 13 kJ/m2 and Eb – 11.3 %). Scanning electron microscopic images of the fracture surface of the composites were suggested. Вивчено зразки джутової мішковини, вимоченої ушелаковому спиртовому розчині івисушеної при 333 К протягом 4 годин. Оцінено механічні властивості біокомпозиту, приготовленого ізшести шарів обробленоїмішковини під тиском та температурі 373 К протягом 10 хв. Вивчено вплив низки додатків з різнимвмістомсечовини (від 0,25 до30 %мас.) урозчині шелаку в метанолі на такі механічні властивості біокомпозиту, як межа міцності при розриванні та згинанні (ММР і ММЗ), модуль розривання і згинання (МР і МЗ), подовження при розриванні (ПР) та ударну в‘язкість (УВ). Встановлено, що найкращі механічні властивості (ММР-79 МПа, ММЗ-74МПа, МР-7ГПа, ПР-11,3 %, УВ-13 кДж/м 2 ) проявляє біокомпозит із вмістом сечовини 0,5 % при тривалості томлення 2 хв. З використанням скануючої електронної мікроскопії наведені зображення поверхні розривання композитів.
Приготування і характеристика зміцнених шелакових біокомпозитів з джутового волокна: вплив додатків
Keywords: jute; shellac; biocomposite; mechanical properties; urea; джут; шелак; біокомпозит; механічні властивості